Limb movements during sleep in children: effects of age, sex, and iron status in more than 1,000 patients referred to a pediatric sleep center - Al-Shawwa, Baha (J Clin Sleep Med, 2020)
STUDY OBJECTIVES: Limb movements during sleep (LMS) and periodic limb movements during sleep (PLMS) have been shown to vary by age in children. In the current study, we examined this relationship in more detail in a large clinically referred sample adjusting for iron status and sex. METHODS: Retrospective data analysis was done on a large pediatric population who underwent an overnight sleep study and had ferritin levels measured within 30 days of sleep study between May 2013 and October 2017 at pediatric sleep center. Patients with obstructive or central sleep apneas were excluded. RESULTS: A total of 1,070 patients were included in the study, with 60% males. Younger age and male sex were associated with increased PLMS and LMS. In addition, there was an increase in PLMS and LMS during adolescence that subsided at a later age, independent of sex. These associations remained significant in models controlling for ferritin level. Ferritin level, in contrast, was not a significant predictor of PLMS or LMS when controlling for sex and age. CONCLUSIONS: Age and sex may need to be considered when interpreting limb movement indices in pediatric sleep patients regardless of ferritin level. CITATION: Al-Shawwa B, Ehsan Z, Perry GV, Ingram DG. Limb movements during sleep in children: effects of age, sex, and iron status in more than 1,000 patients referred to a pediatric sleep center. J Clin Sleep Med. 2020;16(1):49–54.